Illegal rhino horn trade in Nhi Khe, Viet Nam - Stoner, Sarah (Wildlife crime, 2018)
The village of Nhi Khe in Viet Nam caters to tourists mainly interested in ornamental objects made from rhinoceros horn, rather than medicine. Based on field collection of selling prices, the research finds a much lower average price for raw horn than is commonly reported: about US$26,000 per kilogram, rather than the US$60,000 widely cited. It is unclear whether this difference represents a declining trend in the price of horn, or is simply an artefact of exaggerated claims in the past. If it is the latter, this is disturbing, since inflated values can actually provide an incentive for further wildlife crime. The research also found a further price decline over 26 months of observation, down to about US$18,000, suggesting that supply may have outstripped demand. This could be good news for the rhinoceros, at least in the short term.